2012
DOI: 10.1111/j.1365-2664.2012.02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Creating patches of native flowers facilitates crop pollination in large agricultural fields: mango as a case study

Abstract: Summary1. As cropland increases, fields become progressively isolated from pollinators, leading to declines in pollinator-dependent crop productivity. With the rise in demand for pollinatordependent foods, such productivity losses may accelerate conversion of natural areas to cropland. Pollination-compensation measures involving managed pollinators or hand pollination are not always optimal or are too costly. Introducing areas of native vegetation within cropland has been proposed as a way to supplement crop p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 39 publications
9
145
0
2
Order By: Relevance
“…Evidence is building for the susceptibility of wild bee communities to pesticides in agricultural fields and landscapes [18,55,59,70,72]. Our findings suggest that heavy use of conventional pesticides, even some traditionally viewed as benign [39], can render our crops net sinks for bee populations.…”
Section: Discussionmentioning
confidence: 80%
“…Evidence is building for the susceptibility of wild bee communities to pesticides in agricultural fields and landscapes [18,55,59,70,72]. Our findings suggest that heavy use of conventional pesticides, even some traditionally viewed as benign [39], can render our crops net sinks for bee populations.…”
Section: Discussionmentioning
confidence: 80%
“…A few studies have considered the consequences of distance from natural habitats on within-crop plant-pollinator networks (Carvalheiro et al, 2010(Carvalheiro et al, , 2012). These studies demonstrate that the diversity of pollinators on crops declines with increasing distance to natural habitats, both in mango plantations (Carvalheiro et al, 2010) and in sunflower fields (Carvalheiro et al, 2012, see also Ricketts et al, 2008. When distance to natural habitats increases, the decrease in pollinator diversity also leads to a reduction of network complexity up to the single couple MFCmanaged honeybees (see Box 3).…”
Section: The Case Of Plantsmentioning
confidence: 99%
“…Previous studies have found that natural vegetation in the area is a source of both flower visitors (Carvalheiro et al, 2010(Carvalheiro et al, , 2012Geslin et al, 2016) and natural enemies of crop pests (Henri et al, 2015;Morgan et al, 2017) in mango fields. Mangos in turn have been shown to harbour pests that can spill over into natural vegetation (Moxley et al, 2017), and it is likely that pollinators, too, spill over into natural vegetation.…”
Section: Introductionmentioning
confidence: 99%